Long‐term effects of habitat fragmentation on mating patterns and gene flow of a tropical dry forest tree, Ceiba aesculifolia (Malvaceae: Bombacoideae)1. Issue 6 (1st June 2013) - Quesada, Mauricio; Herrerías‐Diego, Yvonne; Lobo, Jorge A.; Sánchez‐Montoya, Gumersindo; Rosas, Fernando; Aguilar, Ramiro
Abstract : Premise of the study: Tropical forest loss and fragmentation isolate and reduce the size of remnant populations with negative consequences for mating patterns and genetic structure of plant species. In a 4‐yr study, we determined the effect of fragmentation on mating patterns and pollen pool genetic structure of the tropical tree Ceiba aesculifolia in two habitat conditions: isolated trees in disturbed areas (≤3 trees/ha), and trees (≥6 trees/ha) in undisturbed mature forest. Methods: Using six allozyme loci, we estimated the outcrossing rate ( t m ), the mean relatedness of progeny ( r p ) within and between fruits, the degree of genetic structure of pollen pools (Φft ), and the effective number of pollen donors ( N ep ). Key results: The outcrossing rates reflected a strict self‐incompatible species. Relatedness of progeny within fruits was similar for all populations, revealing single sires within fruits. However, relatedness of progeny between fruits within trees was consistently greater for trees in fragmented conditions across 4 yr. We found high levels of genetic structure of pollen pools in all populations with more structure in isolated trees. The effective number of pollen donors was greater for trees in undisturbed forest than in disturbed conditions. Conclusions: Our study showed that the progeny produced by isolated trees in disturbed habitats are sired by a fraction of the diversity of pollen donors found in conserved forests. The foraging behavior of bats limits the exchange of pollen between trees, causing higher levels of progeny relatedness in isolated trees.